Effects of drug and exercise intervention on functional capacity and quality of life in heart failure with preserved ejection fraction: A meta-analysis of randomized controlled trials. (January 2016) - Fukuta, Hidekatsu; Goto, Toshihiko; Wakami, Kazuaki; Ohte, Nobuyuki
Background: Patients with heart failure with preserved ejection fraction (HFpEF) are often elderly and their primary chronic symptom is severe exercise intolerance that results in a reduced quality of life (QOL).Thus, improvement of exercise capacity and QOL presents an important clinical outcome in HFpEF patients. Although the effects of interventions such as cardiovascular drugs and exercise training on exercise capacity and QOL in HFpEF patients have been examined in a number of clinical trials, the results are inconsistent due in part to limited power with small sample sizes. We aimed to conduct a meta-analysis of the randomized controlled trial (RCT)s on the effect of drug or exercise intervention on exercise capacity and QOL in HFpEF patients. Method and results: The search of electronic databases identified five RCTs on exercise (245 patients) and eight RCTs on cardiovascular drugs (1080 patients). The pooled analysis showed that exercise training improved peak exercise oxygen uptake (VO2 ) (weighted mean difference (WMD) 2.283, 95% confidence interval (CI)) (1.318–3.248) ml/min/kg), six-minute walk distance (6MWD) (30.275 m (4.315–56.234)), and Minnesota Living with Heart Failure Questionnaire (MLHFQ) total score (8.974 points (3.321–14.627)) compared with usual care. In contrast, drug intervention did not improve peak VO2 (WMD (95% CI), –0.393 (−1.005–0.220) ml/min/kg), 6MWD (−9.463 (−21.455–2.530) m), or MLHFQ total score (1.042 (−0.982–3.066) point) compared with placebo or no treatment. Conclusion: Our meta-analysis indicates that exercise training may be a therapeutic option to improve functional capacity and QOL in HFpEF patients.